Successfully reported this slideshow.
Upcoming SlideShare
×

38,918 views

Published on

• Full Name
Comment goes here.

Are you sure you want to Yes No
• I've Saved Over \$400 On Batteries! I can't believe how simple your reconditioning steps are! My old (and once dead) car batteries, cell phone battery, drill battery, camera battery and tons of other batteries are all reconditioned and working great again! Since starting your program I've saved over \$400 on batteries! ▲▲▲ http://t.cn/AiFAbuQp

Are you sure you want to  Yes  No

Are you sure you want to  Yes  No
• what is this, there is too much going on,

Are you sure you want to  Yes  No

1. 1. • A quadratic function (f) is a function that has the form as f(x) = ax2 + bx + c where a, b and c are real numbers and a not equal to zero (or a ≠ 0). • The graph of the quadratic function is called a parabola. It is a "U" or “n” shaped curve that may open up or down depending on the sign of coefficient a. Any equation that has 2 as the largest exponent of x is a quadratic function.
2. 2. ☺Forms of Quadratic functions: * Quadratic functions can be expressed in 3 forms: 1.  General form: f (x) = ax2 + bx + c 2.  Vertex form: f (x)= a(x - h)2 + k (where h and k are the x and y coordinates of the vertex) 3.  Factored form: f(x)= a(x - r1) (x - r2)
3. 3. 1. General form •  Form : f(x) = ax2+ bx+ c •  General form is always written with the x2 term first, followed by the x term, and the constant term last. a, b, and c are called the coefficients of the equation. It is possible for the b and/or c coefficient to equal zero. Examples of some quadratic functions in standard form are: a. f(x) = 2x2 + 3x – 4 (where a = 2, b = 3, c = -4) b. f(x) =x2 – 4 (where a = 1, b = 0, c = -4) c. f(x)= x2 ( where a = 1, b and c = 0) d. f(x)= x2 – 8x (where a = ½, b = -8, c = 0).
4. 4. 2. Vertex Form •  Form: f(x) = a(x - h)2 + k where the point (h, k) is the vertex of the parabola. •  Vertex form or graphing form of a parabola. •  Examples: a. 2(x - 2)2 + 5 (where a = 2, h = 2, and k = 5) b. (x + 5)2 (where a = 1, h = -5, k = 0)
5. 5. 3.Factored Form •  Form: a(x - r1) (x - r2) where r1 and r2 are the roots of the equation. •  Examples: a. (x - 1)(x - 2) b. 2(x - 3)(x - 4) or (2x - 3)(x - 4)
6. 6. Discriminant •  Quadratic formula: If ax2 + bx + c, a ≠ 0, x = •  The value contained in the square root of the quadratic formula is called the discriminant, and is often represented by ∆ = b2 – 4ac. * b2 – 4ac > 0 → There are 2 roots x1,2= . * b2 – 4ac = 0 → There is 1 real root, x = -b/2a. * b2 – 4ac < 0 → There are no real roots.
7. 7. Using Quadratic Formula •  A general formula for solving quadratic equations, known as the quadratic formula, is written as: •  To solve quadratic equations of the form ax2+ bx+ c, substitute the coefficients a, b, and c in to the quadratic formula. 1.  Exercise: Solve 4x2 – 5x + 1 = 0 using the quadratic formula ∆ = b2 – 4ac= 52 – 4(4)(1) = 25 – 16 = 9 => = =±3 x x1 = 1 or x2 = 1/4
8. 8. Using Factoring •  Convert from general form, f(x) = ax2 + bx + c to factored form, a(x - x1) (x - x2) : + Example 1: Solve x2+ 2x = 15 by factoring => x2 + 2x – 15 = 0 (General form) (x + 5)(x - 3) = 0 (Factoring form) x+5=0 or x–3=0 x = -5 or x=3 → Thus, the solution to the quadratic equation is x = -5 or x = 3. + Example 2: Solve x2 + 5x – 9 = -3 by factoring => x2 + 5x – 6 = 0 (General form) (x – 1)(x + 6) = 0 (Factoring form) x–1=0 or x+6=0 x=1 or x = -6 → Thus, the solution to the quadratic equation is x = 1 or x = -6.
9. 9. Using Completing the Square •  Converting from the general form f(x) = ax2+ bx+ c to a statement of the vertex form f(x)= a(x - h)2 + k. •  When quadratic equations cannot be solved by factoring, they can be solved by the method of completing the squares. •  Example: Solve x2 + 4x – 26 = 0 by completing the square •  (x2 + 4x + 4 – 4) – 26 = 0 (General form) •  (x + 2)2 – 4 – 26 = 0 •  (x + 2)2 – 30 = 0 (Vertex form) •  (x + 2)2 = 30 •  x + 2 = •  x =-2 •  x =-2+ or x = - 2 -
10. 10. Application to higher-degree equations •  Example: x4 + 4x2 - 5 = 0 –  The equation above can be written as: –  (x2)2 + 4(x2) - 5 = 0 –  (Quadratic function with exponent x = 2) –  Solve: ./ Substitute x2 = P P2 + 4P - 5 =0 (P + 5)(P - 1) = 0 P = -5 or P=1 ./ Re-substitute P = x2 => P = -5 = x2 = no roots => P = 1 = x2 => x = ± 1
11. 11. The Graph of Quadratic Equation •  The graph of quadratic equation in the form f(x) = ax2+ bx+ c is a parabola. The parts of the graph of the parabola are determined by the values of a, b, and c. •  The most meaningful points of the graph of a parabola are: 1. x-intercepts: The x-intercepts, if any, are also called the roots of the function. They are meaningful specifically as the zeroes of the function, but also represent the two roots for any value of . 2. y-intercept: The importance of the y-intercept is usually as an initial value or initial condition for some state of an experiment, especially one where the independent variable represents time. 3. Vertex: The vertex represents the maximum (or minimum) value of the function, and is very important in calculus and many natural phenomena.
12. 12. X-intercepts •  The x intercepts of the graph of a quadratic function f given by y = ax2 + bx + c •  The x-intercepts are the solutions to the equation ax2 + bx + c = 0 •  The x-intercept in the equation f(x) = ax2 + bx + c, can be found in basically two ways, factoring or the quadratic formula. •  * Factoring: If f(x) = y = ax2 + bx + c can be factored into the form y = a(x – r1)(x – r2) , then the x-intercepts are r1 and r2 . •  Example: y = x2 - 3x - 18 => 0 = x2 – 3x – 18 (Set y = 0 to find the x – intercept) 0 = (x – 6)(x + 3) (Factor) x – 6 = 0 or x + 3 = 0 x = 6 or x = -3 ( Solved the equation => x – int. = (6, 0) ; (-3, 0) ) •  * Quadratic formula: For any function in the form y = ax2 + bx + c, x- intercepts are given by: ( , 0) •  Example: y = 2x2 + 5x + 3 (a = 2; b = 5; c = 3 ) => 0 = 2x2 + 5x + 3 (Set y = 0 to find x – int. ) x = ( Using Quadratic formula to solve the equation) x = -5 ±1/4 => x = -19/4 or x = -21/4 (Simplified the equation => x – int. = (-21/4, 0) or (-19/4, 0)).
13. 13. Y-intercept •  The y intercept of the graph of a quadratic function is given by f(0) = c or y-intercept = (0,c). •  Example: Find the y intercept of the following equations: –  A) x2 + 2x + 26 –  B) 16x2 – 3x – 59 –  C) 10x2 + 5x – 10/7 * Solution: A) Substitute 0 for x as f(x) = f(0) = x2 + 2x + 26 => f(0) = c = 26. The y intercept is at (0, 26). B) Same method as A). f(0) = -59. The y-int. is (0, -59) C) f(0) = -10/7. The y-int. is (0, -10/7)
14. 14. The Vertex •  The vertex can be found by completing the square, or by using the expression derived from completing the square on the general form. •  Formula given by: y = ax2 + bx + c So the vertex is •  Example: h = -12x2 + 168x – 38 •  => -b/2a = -168/2(-12) = 7 (applied the formula to find x-coordinate of vertex of the quadratic equation). •  Substitute for x (x = 7) into the original equation. We have that: h = -12(7)2 + 168(7) – 38 = 550 •  Thus, the vertex of the equation is (7, 550).
15. 15. Graphing Parabola •  There are several steps to do before we sketch a graph of parabola of the quadratic equation. •  The most easiest way to sketch the graph is from vertex form. •  Steps: 1. We need to check whether the graph is concave up if a > 0 (U- shaped) or concave down if a < 0(n-shaped). 2. We need to find the vertex of the equation by the formula x =-b/2a or by the vertex form. 3. We need to find the values of x and y intercepts. + Substitute x = 0 into the equation then find the coordinate of y value. + Let y = 0 then find the values of x.
16. 16. Graphing Parabola •  Graph the function f(x) = 2x2 + 8x +7 Solution: 1.  Write the function f(x) = 2x2 + 8x + 7 in the form f(x) = a (x - h) 2 + k by completing the square. (h, k) f (x) = 2x2 + 8x + 7 => f (x) = 2 (x2 + 4x) + 7 => f (x) = 2 (x2 + 4x + 4) + 7 – 8 => f (x) = 2 (x + 2)2 – 1 3.  The function f (x) = 2x2 + 8x + 7 has vertex at (-2, -1) with a horizontal shift of 2 units to the left and a vertical shift of one unit downward. Also since a = 2 > 0 then the graph is concave up. 4.  The x-intercept of the function are determined by letting f (x) = 2 (x + 2)2 – 1 = 0 and solving for x as illustrated below:
17. 17. Continued f (x) = 2 (x + 2)2 – 1 = 0 => (x + 2)2 = ½ => x + 2 = ± √½ = ± 1/√2 => x = -2 ± (1/√2) 4. The y-intercept is f (0) = 2 (0 + 2)2 – 1 = 7 * The graph of f (x) = 2x2 + 8x +7 is illustrated below: